2021
DOI: 10.1111/jcmm.16567
|View full text |Cite
|
Sign up to set email alerts
|

CIRBP promotes ferroptosis by interacting with ELAVL1 and activating ferritinophagy during renal ischaemia‐reperfusion injury

Abstract: Renal ischaemia‐reperfusion (IR) is a major cause of acute kidney injury (AKI). Cold‐inducible RNA‐binding protein (CIRBP) may contribute to AKI because its deficiency protects against renal IR injury in a mechanism believed to involve ferroptosis. We aimed to investigate whether ferroptosis is associated with CIRBP‐mediated renal damage. The differential expression of CIRBP was examined in tubular epithelial (HK2) cells during hypoxia‐reoxygenation (HR) or in response to erastin, an inducer of ferroptosis. CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Previous studies have suggested that targeting ferroptosis could prevent tubular injury, regulate the integrity of mitochondria, and alleviate inflammation via immune cells in rodent models of diabetic nephrology or AKI (Fig. 4 ) [ 118 121 ]. However, direct evidence about ferroptosis in the progression of AKI to CKD is lacking, which might be a hot point of research in the future.…”
Section: Ferroptosis In the Aki To Chronic Kidney Disease (Ckd) Progr...mentioning
confidence: 99%
“…Previous studies have suggested that targeting ferroptosis could prevent tubular injury, regulate the integrity of mitochondria, and alleviate inflammation via immune cells in rodent models of diabetic nephrology or AKI (Fig. 4 ) [ 118 121 ]. However, direct evidence about ferroptosis in the progression of AKI to CKD is lacking, which might be a hot point of research in the future.…”
Section: Ferroptosis In the Aki To Chronic Kidney Disease (Ckd) Progr...mentioning
confidence: 99%
“…Although there is a biochemical link between NCOA4-mediated ferritinophagy and ferroptosis, current findings have shown a positive correlation among them (i.e., NCOA4- mediated ferritinophagy can induce ferroptosis) [ 65 67 ]; therefore, the relationship between remains controversial. For example, NCOA4 levels varied by ferroptosis inducer, with increased expression reported in hepatic stellate cells (HSCs) after sorafenib treatment, no differential expression in pancreatic cancer cells after elastin treatment, and elastin therapy resulted in even lower levels in MEFs or artesunate treatment in HSCs [ 62 ].…”
Section: Ferroptosis Relation With Other Rcdsmentioning
confidence: 99%
“…This further confirmed that cold induction could promote the process of ferroptosis by inducing the expression of CIRBP and then regulating key factors such as p53 and GPX4. Ferroptosis inducer erastin or hypoxia-reoxygenation (HR) treatment induced renal tubular epithelial cells to express CIRBP, and silencing of CIRBP inhibited ferroptosis induced by HR or erastin [ 20 ]. Therefore, CIRBP is also a key factor regulating the progression of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%